The Asian ‘Poverty Miracle’ 2016
DOI: 10.4337/9781785369155.00012
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and vulnerability to poverty: an empirical investigation in rural Indonesia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Fujii (2016) estimated the effects of climate change on poverty in Indonesia using econometric analysis. The results showed that climate change increases temperature and sea tides which create poverty vulnerability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fujii (2016) estimated the effects of climate change on poverty in Indonesia using econometric analysis. The results showed that climate change increases temperature and sea tides which create poverty vulnerability.…”
Section: Literature Reviewmentioning
confidence: 99%